Mapping land cover in complex Mediterranean landscapes using Landsat: Improved classification accuracies from integrating multi-seasonal and synthetic imagery - Senf, Cornelius; Leitão, Pedro J.; Pflugmacher, Dirk; van der Linden, Sebastian; Hostert, Patrick (Remote Sensing of Environment, 2015)
Low-intensity farming systems are of great importance for biodiversity in Europe, but they are often affected by soil degradation or economic pressure, leading to either land abandonment or intensification of agriculture. These changes in land use influence local biodiversity patterns and require annual monitoring of land cover. To accuratelymap landcover in such spatio-temporal complex landscapes, it isimportant to capture their phenolog- ical dynamics andfine spatial heterogeneity.Multi-seasonal analyses using optical sensorswith amediumspatial resolution from10 to 60m(e.g. Landsat) have been used for this task, but data availability can be scarce due to cloud cover, sub-optimal acquisition schedules and data archive access restrictions. Combining coarse spatial res- olution data fromtheMODerate-resolution Imaging Spectroradiometer(MODIS) and Landsat provides opportu- nities to close these gaps by simulating Landsat-like images atMODIS temporal resolution. In this study,we test whether and by what degree land cover maps of complex Mediterranean landscapes improve by integrating multi-seasonal Landsat imagery, as well aswhether STARFM-simulated imagery can be usedwhenever original multi-seasonal Landsat observations are unavailable. Therefore, we develop different classification scenarios based on seasonally varying data availability and based on original and simulated Landsat data. Results show that multi-seasonal Landsat data from spring and early autumn are crucial for achieving satisfying mapping accuracies (overall accuracy 74.5%). Using synthetic Landsat imagery increases classification accuracy compared to using single-date Landsat data, but accuracieswere never as good as a classification based on original data.We conclude thatmulti-seasonal data is essential for mapping complex Mediterranean landscapes and that STARFM can be used to compensate for missing Landsat observations. However, if Landsat data availability is sufficient to cover all phenologically important dates, we suggest relying solely on Landsat.
Keywords: image classification; Landsat; Mediterranean; Phenology; Pseudo-steppe; STARFM

Assessing road effects on bats: the role of landscape, road features, and bat activity on road-kills - Medinas, Denis; Marques, J.Tiago; Mira, António (Ecological Research, 2013)
Recent studies suggest that roads can signifi- cantly impact bat populations. Though bats are one of the most threatened groups of European vertebrates, studies aiming to quantify bat mortality and determine the main factors driving it remain scarce. Between March 16 and October 31 of 2009, we surveyed road-killed bats daily along a 51-km-long transect that incorporates dif- ferent types of roads in southern Portugal. We found 154 road-killed bats of 11 species. The two most common species in the study area, Pipistrellus kuhlii and P. pyg- maeus, were also the most commonly identified road-kill, representing 72 % of the total specimens collected. About two-thirds of the total mortality occurred between mid July and late September, peaking in the second half of August.We also recorded casualties of threatened and rare species, including Miniopterus schreibersii, Rhinolo- phus ferrumequinum, R. hipposideros, Barbastella barba- stellus, and Nyctalus leisleri. These species were found mostly in early autumn, corresponding to the mating and swarming periods. Landscape features were the most important variable subset for explaining bat casualties. Road stretches crossing or in the vicinity of high-quality habitats for bats—including dense Mediterranean woodland (‘‘montado’’) areas, water courses with ripar- ian gallery, and water reservoirs—yielded a significantly higher number of casualties. Additionally, more road- killed bats were recorded on high-traffic road stretches with viaducts, in areas of higher bat activity and near known roosts.
Keywords: Bat activity; mediterranean landscape; Phenology; Road traffic; Road-kill modeling

Evaluation of the potential of MODIS satellite data to predict vegetation phenology in different biomes: An investigation using ground-based NDVI measurements - Hmimina, G; Dufrêne, E; Pontailler, J.-Y.; Delpierre, N; Aubinet, M; Caquet, B; de Grandcourt, A; Burban, B; Flechard, C; GRANIER, a; Gross, P; Heinesch, B; et al. (Remote Sensing of Environment, 2013)
Abstract Vegetation phenology is the study of the timing of seasonal events that are considered to be the result of adaptive responses to climate variations on short and long time scales. In the field of remote sensing of vegetation phenology, phenological metrics are derived from time series of optical data. For that purpose, considerable effort has been specifically focused on developing noise reduction and cloud-contaminated data removal techniques to improve the quality of remotely-sensed time series. Comparative studies between time series composed of satellite data acquired under clear and cloudy conditions and from radiometric data obtained with high accuracy from ground-based measurements constitute a direct and effective way to assess the operational use and limitations of remote sensing for predicting the main plant phenological events. In the present paper, we sought to explicitly evaluate the potential use of MODerate resolution Imaging Spectroradiometer (MODIS) remote sensing data for monitoring the seasonal dynamics of different types of vegetation cover that are representative of the major terrestrial biomes, including temperate deciduous forests, evergreen forests, African savannah, and crops. After cloud screening and filtering, we compared the temporal patterns and phenological metrics derived from in situ NDVI time series and from MODIS daily and 16-composite products. We also evaluated the effects of residual noise and the influence of data gaps in MODIS NDVI time series on the identification of the most relevant metrics for vegetation phenology monitoring. The results show that the inflexion points of a model fitted to a MODIS NDVI time series allow accurate estimates of the onset of greenness in the spring and the onset of yellowing in the autumn in deciduous forests (RMSE ≤ one week). Phenological metrics identical to those provided with the MODIS Global Vegetation Phenology product (MDC12Q2) are less robust to data gaps, and they can be subject to large biases of approximately two weeks or more during the autumn phenological transitions. In the evergreen forests, in situ NDVI time series describe the phenology with high fidelity despite small temporal changes in the canopy foliage. However, MODIS is unable to provide consistent phenological patterns. In crops and savannah, MODIS NDVI time series reproduce the general temporal patterns of phenology, but significant discrepancies appear between MODIS and ground-based NDVI time series during very localized periods of time depending on the weather conditions and spatial heterogeneity within the MODIS pixel. In the rainforest, the temporal pattern exhibited by a MODIS 16-day composite NDVI time series is more likely due to a pattern of noise in the NDVI data structure according to both rainy and dry seasons rather than to phenological changes. More investigations are needed, but in all cases, this result leads us to conclude that MODIS time series in tropical rainforests should be interpreted with great caution.
Keywords: Crops; Deciduous forests; evergreen forests; Ground-based NDVI; MODIS; Phenology

Fine Root Seasonal Dynamics, Plasticity, and Mycorrhization in 2 Coexisting Mediterranean Oaks with Contrasting Aboveground Phenology - Coll, Lluís; Camarero, Araid; Aragón, Juan Martínez De; Camarero, Jesús Julio; Martínez de Aragón, Juan; Camarero, Araid; Aragón, Juan Martínez De (Ecoscience, 2012)
To advance understanding of the mechanisms underpinning the coexistence of Mediterranean oak species, we conducted a year-long analysis of the production, architecture, and mycorrhization status of the fine roots of a mixed evergreen (Quercus ilex) and winter deciduous (Quercus faginea) oak stand. We used the ingrowth bag technique to sample the fine roots produced by each species in spring, summer, and winter. For each season, root architecture traits (specific root length, root diameter, root tips) and variables associated to root ectomycorrhizal status were measured in the laboratory. Results showed a marked seasonality in the fine root architecture, including more fine root tips and longer roots per unit of weight formed in spring and summer, revealing a capacity in Mediterranean oak species to modify root architecture in spring and suggesting the possibility of increased resource capture in summer. Fine root ectomycorrhizal status was comparable between species and also showed marked seasonality: we found a high percentage of roots colonized by dead ectomycorrhizas in winter but low ectomycorrhizal colonization rates in summer. Quercus ilex produced greater amounts of fine roots than Q. faginea (particularly during spring), suggesting greater competitive ability in the former species for belowground resources.
Keywords: architecture et le statut; Chênes; coexistence d; des mécanismes supportant la; Ectomycorrhizae; espèces méditerranéennes de; et caduques; feuilles persistantes; fine roots; l; mixte de chênes à; mycorhizien des radicelles d; nous avons analysé sur; nous avons utilisé la; Phenology; pour accroître notre compréhension; Quercus faginea; Quercus ilex; résumé; root traits; technique du sac; un peuplement; une année la production

Forest microhabitats differentially influence seedling phenology of two co-existing Mediterranean oak species - Monnier, Yogan; Prévosto, Bernard; Ripert, Christian; Corbani, Aude C.; Fernandez, Catherine (Journal of Vegetation Science, 2012)
Question How do forest microhabitats impact seasonal microclimate conditions and phenological seedling strategies in two co-occurring Mediterranean Quercus species with different leaf habits? Location Pinus halepensis woodlands, Provence, SE France. Methods Ninety sets of three acorns of Quercus ilex (evergreen) or Quercus pubescens (winter-deciduous) were sown under various P. halepensis canopy cover conditions. Canopy cover and litter depth were measured at each sowing point, and soil moisture and temperature were measured twice monthly. Seedling phenology and aerial development were monitored during the second growing season under different microhabitats. Results During rainy periods, soil moisture was higher under open canopy and thinner litter layers, whereas during summer drought soil moisture was higher under dense canopy and thicker litter layers. Quercus pubescens seedlings had higher growth activity than Q. ilex before summer drought, whereas the pattern reversed during autumnal growth. Dense canopy cover strongly delayed budburst and decreased foliar development in Q. pubescens, which was more affected than Q. ilex. Depending on species phenology, litter thickness can influence height growth of flushes during early summer. Conclusions Quercus pubescens has a phenological strategy to allow development of maximal foliar area before summer drought, a typical growth strategy of Mediterranean winter-deciduous species. In contrast, later phenological activity of evergreen Q. ilex enables it to cope with the dry period and capitalize on autumnal precipitation events. Dense cover acts as shelter in the dry season but can reduce soil moisture during wetter seasons. In contrast to Q. ilex, Q. pubescens appeared strongly dependent on canopy cover, suggesting that Q. ilex has a larger regeneration niche in Aleppo pine woodlands. In the context of global change, this ‘microhabitat effect’ on species-specific phenological strategy underlines the need to consider effects of local environmental conditions on regenerating species.
Keywords: Canopy; litter; Phenology; Quercus ilex; Quercus pubescens; Soil moisture; Survival

Ground-based Network of NDVI measurements for tracking temporal dynamics of canopy structure and vegetation phenology in different biomes - Soudani, K; Hmimina, G; Delpierre, N; Pontailler, J.-Y.; Aubinet, M; Bonal, D; Caquet, B; de Grandcourt, A; Burban, B; Flechard, C; Guyon, D; GRANIER, a; et al. (Remote Sensing of Environment, 2012)
Plant phenology characterises the seasonal cyclicity of biological events such as budburst, ﬂowering, fructiﬁ- cation, leaf senescence and leaf fall. These biological events are genetically pre-determined but also strongly modulated by climatic conditions, particularly temperature, daylength and water availability. Therefore, the timing of these events is considered as a good indicator of climate change impacts and as a key parameter for understanding and modelling vegetation–climate interactions. In situ observations, empirical or bioclimatic models and remotely sensed time-series data constitute the three possible ways for monitoring the timing of plant phenological events. Remote sensing has the advantage of being the only way of surface sampling at high temporal frequency and, in the case of satellite-based remote sensing, over large regions. Nevertheless, exogenous factors, particularly atmospheric conditions, lead to some uncertainties on the seasonal course of surface reﬂectance and cause bias in the identiﬁcation of vegetation phenological events. Since 2005, a network of forest and herbaceous sites has been equipped with laboratory made NDVI sensors to monitor the temporal dynamics of canopy structure and phenology at an intra-daily time step. In this study, we present recent results obtained in several contrasting biomes in France, French Guiana, Belgium and Congo. These sites represent a gradient of vegetation ecosystems: the main evergreen and deciduous forest ecosystems in temperate climate region, an evergreen tropical rain forest in French Guiana, an herbaceous savanna ecosystem in Congo, and a succession of three annual crops in Belgium. In this paper, (1) we provide an accurate description of the seasonal dynamics of vegetation cover in these different ecosystems (2) we identify the most relevant remotely sensed markers from NDVI time-series for determining the dates of the main phenological events that characterize these ecosystems and (3) we discuss the relationships between temporal canopy dynamics and climate factors. In addition to its importance for phenological studies, this ground-based Network of NDVI measurement provides data needed for the calibration and direct validation of satellite observations and products.
Keywords: Crops; Evergreen and deciduous forests; Ground-based NDVI; Herbaceous savanna; NDVI time-series; Phenology; Tropical rain forest

A model to account for variations in production in southern Spain - García-mozo, Herminia; Dominguez-vilches, Eugenio; Galán, Carmen (Annals of Agricultural and Environmental Medicine, 2012)
One of the characteristics of holm-oak acorn production is its high variability among individuals and years. To examine the main causes of this fact, a study was conducted from 1998-2010 in a natural area of holm-oak in southern Spain, where floral phenology, fruit production, fruit size, airborne pollen emission and meteorology factors were analyzed with the ultimate aim of developing a model for forecasting holm-oak yield. Pollen emission during flowering season was the main factor determining the final acorn harvest, but also some meteorological variables played an important role in explaining acorn crop variations, especially humidity and temperature during the months of April and September. The reliability of the proposed model was externally validated using data not included in its construction; validation yielded acceptable results, with a minimum error of estimation. Our results appear to be very useful for planning cropping and pig feeding strategies. Further research could extend the use of airborne pollen counts in forest studies relating to anemophilous species, in order to optimize agricultural policies.
Keywords: acorn production; Aerobiology; Holm oak; model; oak forest; Phenology; pollen; quercus ilex subsp. ballota

Phenological records as a complement to aerobiological data. - Tormo, Rafael; Silva, Inmaculada; Gonzalo, Angela; Moreno, Alfonsa; Pérez, Remedios; Fernández, Santiago (International journal of biometeorology, 2011)
Phenological studies in combination with aerobiological studies enable one to observe the relationship between the release of pollen and its presence in the atmosphere. To obtain a suitable comparison between the daily variation of airborne pollen concentrations and flowering, it is necessary for the level of accuracy of both sets of data to be as similar as possible. To analyse the correlation between locally observed flowering data and pollen counts in pollen traps in order to set pollen information forecasts, pollen was sampled using a Burkard volumetric pollen trap working continuously from May 1993. For the phenological study we selected the main pollen sources of the six pollen types most abundant in our area: Cupressaceae, Platanus, Quercus, Plantago, Olea, and Poaceae with a total of 35 species. We selected seven sites to register flowering or pollination, two with semi-natural vegetation, the rest being urban sites. The sites were visited weekly from March to June in 2007, and from January to June in 2008 and 2009. Pollen shedding was checked at each visit, and recorded as the percentage of flowers or microsporangia in that state. There was an association between flowering phenology and airborne pollen records for some of the pollen types (Platanus, Quercus, Olea and Plantago). Nevertheless, for the other types (Cupressaceae and Poaceae) the flowering and airborne pollen peaks did not coincide, with up to 1 week difference in phase. Some arguments are put forward in explanation of this phenomenon. Phenological studies have shown that airborne pollen results from both local and distant sources, although the pollen peaks usually appear when local sources are shedding the greatest amounts of pollen. Resuspension phenomena are probably more important than long-distance transport in explaining the presence of airborne pollen outside the flowering period. This information could be used to improve pollen forecasts.
Keywords: Aerobiology; Allergy; Forecasting; Phenology; pollen; Pollen trap

Mismatch between the timing of oviposition and the seasonal optimum. The stochastic phenology of Mediterranean acorn weevils - Bonal, Raul; Muñoz, Alberto; MARÍA ESPELTA, JOSEP (Ecological Entomology, 2010)
1. The timing of reproduction is predicted to match the period of maximum food availability. In this sense, the case of many phytophagous insects in temperate regions is very illustrative, as their larvae usually depend on a resource only available for a limited period of time each year. 2. For 3 years the interactions between the weevil Curculio elephas and the Mediterranean Holm oak Quercus ilex were studied. Weevil larvae grow within the acorns, feeding on the cotyledons. The timing of oviposition will determine food availability for the larvae, as acorns stop growing once they are attacked. 3. Acorn temporal growing patterns did not change between years and food availability for larvae was at its highest in October, when temperature was still suitable for larval development. However, oviposition phenology did change between years. In 2002 females oviposited later, larvae grew within larger acorns, and their body mass was significantly higher than in 2003 or 2004, when females oviposited into early acorns. 4. Thus, weevils do not always adjust oviposition to the best possible feeding conditions for their offspring. Rather, they seem to maximise their own lifetime fitness, ovipositing as soon as they emerge in late summer. Emergence, in turn, depends strongly on stochastic events such as summer storms in the Mediterranean region. 5. Under a climate change perspective, the trend towards higher August rainfall recorded in our study area may alter oviposition phenology, with the subsequent cascade effects on weevil body size and fitness
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn; adult emergence; Curculio; oviposition; Phenology; stochastic events; Temperature; timing of reproduction

Phenological trends in southern Spain: A response to climate change - García-Mozo, H.; Mestre, a; Galan, C. (Agricultural and Forest Meteorology, 2010)
The impact of climate change, and particularly of climate warming, is being tracked in many physical and biological systems. Plant phenology is seen as one of the most important bio-indicators, since trends can provide considerable temporal and spatial information regarding ongoing changes. Analyses performed at six sites in southern Spain from 1986 to the present have focused on vegetative and overall reproductive phenology in Olea europaea L., and Vitis vinifera L. and in various species of Quercus spp. and Poaceae. Early results suggest that trends in ﬂowering patterns derived from ﬁeld phenological observations were similar to trends in aerobiological data for most study species, and indicate a trend towards earlier foliation, ﬂowering and fruit ripening. This advance is more evident in arboreal than in herbaceous species. Statistical analysis showed temperature increase was the major factor affecting earlier foliation, ﬂowering and fruit ripening, as well as prompting delayed leaf fall. Herbaceous species were more affected than trees by changes in rainfall records
Keywords: Aerobiology; climate change; Phenology; pollen

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V.; Castro-Díez, P.; Valladares, F. (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Differential and interactive effects of temperature and photoperiod on budburst and carbon reserves in two co-occurring Mediterranean oaks - Sanz-Pérez, V; Castro-Diez, P; Valladares, F (Plant Biology, 2009)
Effects of temperature and photoperiod and their interactions on budburst and on the use of carbon reserves were examined in two Mediterranean oaks differing in wood anatomy and leaf habit. Seedlings of Quercus ilex subsp. ballota (evergreen and diffuse-porous wood) and Q. faginea (semi-deciduous and ring-porous wood) were grown under two temperatures (12 and 19 °C) and two photoperiods (10 and 16 h) in a factorial experiment. In the 16 h photoperiod at 19 °C, photosynthesis was suppressed in half of the seedlings by covering leaves with aluminium foil. The concentration of soluble sugars, starch and lipids in leaves, stems and roots was assessed before and after budburst. Under the 12 °C treatment (mean current temperature in early spring in the Iberian Peninsula), budburst in Q. faginea occurred earlier than in Q. ilex. Higher temperature promoted earlier budburst in both species, mostly under the 16 h photoperiod. This response was less pronounced in Q. faginea because its budburst was also controlled by photoperiod, and because this species needs to construct a new ring of xylem before budburst to supply its growth demands. Therefore, dates of budburst of the two species became closer to each other in the warmer treatment, which might alter competitive relations between the species with changing climate. While Q. ilex relied on carbon reserves for budburst, Q. faginea relied on both carbon reserves and current photoassimilates. The different responses of the two Quercus species to temperature and photoperiod related more to xylem structure than to the source of carbon used for budburst.
Keywords: Global warming; Lipids; Phenology; Quercus faginea; Quercus ilex; soluble sugars; starch; wood anatomy

Regional phenological models for forecasting the start and peak of the Quercus pollen season in Spain - García-Mozo, H.; Chuine, I.; Aira, M.J. J; Belmonte, J.; Bermejo, D.; Díaz de la Guardia, C.; Elvira, B.; Gutiérrez, M.; Rodríguez-Rajo, J.; Ruiz, L.; Trigo, M.M. M; Tormo, R.; et al. (Agricultural and Forest Meteorology, 2008)
he study sought to achieve the broadest possible spatial and temporal predictions by examining genetic variations in the timing of ﬂowering between populations of the Iberian Quercus species using pollen data from 15 sites in Spain. The speciﬁc objective of the study was to develop and ﬁt regional phenological model to predict the ﬂowering start and ﬂowering peak of Quercus species in the Iberian Peninsula by ascertaining whether potentially signiﬁcant genetic variations in the timing of ﬂowering required different phenological models or if, on the contrary, regional models for several localities can explain the variability detected in Quercus phenology in Spain. Model estimates did not vary greatly as a function of environment within similar climate areas where the same species grew; thus, model estimates of the temperature response of individuals growing in similar climate areas did not differ signiﬁcantly. The percentage of variance explained by models was greater in models ﬁtted with local data (75–97%). Nevertheless, acceptable results were also obtained using regional models (55–85%). The lowest value was found for the Simplifed Model including all Spanish sites together (51%).
Keywords: Aerobiology; Modelling; oak forest; Phenology; pollen; Quercus

Regional phenological models for forecasting the start and peak of the Quercus pollen season in Spain - García-Mozo, H.; Chuine, I.; Aira, M. J. J.; Belmonte, J.; Bermejo, D.; Díaz de la Guardia, C.; Elvira, B.; Gutiérrez, M.; Rodríguez-Rajo, J.; Ruiz, L.; Trigo, M. M. M.; Tormo, R.; et al. (Agricultural and Forest Meteorology, 2008)
he study sought to achieve the broadest possible spatial and temporal predictions by examining genetic variations in the timing of ﬂowering between populations of the Iberian Quercus species using pollen data from 15 sites in Spain. The speciﬁc objective of the study was to develop and ﬁt regional phenological model to predict the ﬂowering start and ﬂowering peak of Quercus species in the Iberian Peninsula by ascertaining whether potentially signiﬁcant genetic variations in the timing of ﬂowering required different phenological models or if, on the contrary, regional models for several localities can explain the variability detected in Quercus phenology in Spain. Model estimates did not vary greatly as a function of environment within similar climate areas where the same species grew; thus, model estimates of the temperature response of individuals growing in similar climate areas did not differ signiﬁcantly. The percentage of variance explained by models was greater in models ﬁtted with local data (75–97%). Nevertheless, acceptable results were also obtained using regional models (55–85%). The lowest value was found for the Simplifed Model including all Spanish sites together (51%).
Keywords: Aerobiology; Modelling; oak forest; Phenology; pollen; Quercus

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 18643937
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Seasonal variability of dry matter content and its relationship with shoot growth and nonstructural carbohydrates - Palacio, Sara; Milla, Rubén; Albuixech, Jorge; Pérez-Rontomé, Carmen; Camarero, Jesús Julio; Maestro, Melchor; Montserrat-Martí, Gabriel (New Phytologist, 2008)
* • This study assesses how different phases of shoot growth underlie seasonal change in leaf and stem dry matter content (LDMC and SDMC, respectively) of 12 woody Mediterranean species. The relationship between LDMC and nonstructural carbohydrate (NSC) concentrations is also explored and the seasonal vs interspecies variability of LDMC compared. * • LDMC, SDMC and shoot elongation rate (SER) were measured on a monthly basis for a minimum of 12 months. Bud growth rate (BGR) and NSC concentrations were also assessed in several of the study species. * • LDMC and SDMC decreased during shoot elongation in spring and increased in summer, showing a significant negative correlation with SER, but were unrelated to BGR. Half of the species analysed showed a positive relationship between LDMC and NSC. Seasonal fluctuations of LDMC within species were higher than interspecies differences, and species ranking was significantly affected by the month of sampling, except during winter months. * • Seasonal changes in LDMC and SDMC are mainly related to shoot elongation phenology, and NSC sink–source relationships between old and growing organs can explain this relationship in some species. Owing to the high seasonal variability in LDMC, it is recommended that samples for comparative purposes should be collected as close to the winter as possible.
Keywords: Carbohydrate Metabolism; functional classifications; leaf dry matter content (LDMC); leaf traits; leaf water status; Mediterranean; Phenology; Plant Development; Plant Leaves; Plant Leaves: growth & development; Plant Leaves: metabolism; Plant Shoots; Plant Shoots: growth & development; Plant Shoots: metabolism; Plant Stems; Plant Stems: growth & development; Plant Stems: metabolism; Plants; Plants: metabolism; Seasons; shoot growth; Species Specificity

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M.T. T; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M. T. T.; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Use of Quercus ilex subsp. ballota phenological and pollen-production data for interpreting Quercus pollen curves - Jato, V; Rodríguez-Rajo, F J; Aira, M J (Aerobiologia, 2007)
Although aerobiological data are often used in phenological research as an indicator of ﬂowering, airborne pollen concentrations are inﬂuenced by a number of factors that could affect pollen curves. This paper reports on a study of various aspects of reproductive biology in Q. ilex subsp. ballota, together with environmental factors inﬂuencing pollen release and transport, with a view of achieving reliable interpretation of Quercus pollen curves in Ourense (NW Spain). Aerobiological data were recorded from 2002 to 2004 at two sites in the province of Ourense. From 1st February to the end of the ﬂowering period, phenological observations were carried out on 19 trees from the Q. ilex subsp. ballota population found in the Ourense area. Pollen production was calculated for the same trees. The chilling and heating requirements for triggering development were also calculated. The mean ﬂowering period lasted 11-15 days. Reduced pollen output per catkin and, especially, a reduced number of catkins per tree in 2003 and 2004, prompted a marked decline in overall pollen production. Major differences observed in Q. ilex subsp. ballota pollen curves were attributed to the considerable inﬂuence both of weather conditions during pollination and pollen production. In years with high pollen production and weather conditions favouring pollen release, Q. ilex subsp. ballota contributed almost 10% to the total Quercus pollen curve. Around 20% of the pollen trapped was captured before or after ﬂowering periods.
Keywords: airborne pollen; Phenology; pollen production; Quercus

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.81710.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Sensitivity of water and carbon fluxes to climate changes from 1960 to 2100 in European forest ecosystems - Davi, H.; Dufrêne, E.; François, C.; Le Maire, G.; Loustau, D.; Bosc, A.; Rambal, S.; Granier, A.; Moors, E. (Agricultural and Forest Meteorology, 2006)
The effects of climate changes on carbon and water ﬂuxes are quantiﬁed using a physiologically multi-layer, process-based model containing a carbon allocation model and coupled with a soil model (CASTANEA). The model is ﬁrst evaluated on four EUROFLUX sites using eddy covariance data, which provide estimates of carbon and water ﬂuxes at the ecosystem scale. It correctly reproduces the diurnal ﬂuxes and the seasonal pattern. Thereafter simulations were conducted on six French forest ecosystems representative of three climatic areas (oceanic, continental and Mediterranean areas) dominated by deciduous species (Fagus sylvatica, Quercus robur), coniferous species (Pinus pinaster, Pinus sylvestris) or sclerophyllous evergreen species (Quercus ilex). The model is driven by the results of a meteorological model (ARPEGE) following the B2 scenario of IPCC. From 1960 to 2100, the average temperature increases by 3.1 8C (30%) and the rainfall during summer decreases by 68 mm (27%). For all the sites, between the two periods, the simulations predict on average a gross primary production (GPP) increase of 513 g(C) m 2 (+38%). This increase is relatively steep until 2020, followed by a slowing down of the GPP rise due to an increase of the effect of water stress. Contrary to GPP, the ecosystem respiration (Reco ) raises at a constant rate (350 g(C) m 2 i.e. 31% from 1960 to 2100). The dynamics of the net ecosystem productivity (GPP minus Reco ) is the consequence of the effect on both GPP and Reco and differs per site. The ecosystems always remain carbon sinks; however the sink strength globally decreases for coniferous (8%), increases for sclerophyllous evergreen (+34%) and strongly increases for deciduous forest (+67%) that largely beneﬁts by the lengthening of the foliated period. The separately quantiﬁed effects of the main variables (temperature, length of foliated season, CO2 fertilization, drought effect), show that the magnitude of these effects depends on the species and the climatic zone
Keywords: canopy scale; carbon sink; climate change; forest ecosystems; Phenology

Sensitivity of water and carbon fluxes to climate changes from 1960 to 2100 in European forest ecosystems - Davi, H; Dufrêne, E; Francois, C; Le Maire, G; Loustau, D; Bosc, A; Rambal, S; GRANIER, a; Moors, E (Agricultural and Forest Meteorology, 2006)
The effects of climate changes on carbon and water ﬂuxes are quantiﬁed using a physiologically multi-layer, process-based model containing a carbon allocation model and coupled with a soil model (CASTANEA). The model is ﬁrst evaluated on four EUROFLUX sites using eddy covariance data, which provide estimates of carbon and water ﬂuxes at the ecosystem scale. It correctly reproduces the diurnal ﬂuxes and the seasonal pattern. Thereafter simulations were conducted on six French forest ecosystems representative of three climatic areas (oceanic, continental and Mediterranean areas) dominated by deciduous species (Fagus sylvatica, Quercus robur), coniferous species (Pinus pinaster, Pinus sylvestris) or sclerophyllous evergreen species (Quercus ilex). The model is driven by the results of a meteorological model (ARPEGE) following the B2 scenario of IPCC. From 1960 to 2100, the average temperature increases by 3.1 8C (30%) and the rainfall during summer decreases by 68 mm (27%). For all the sites, between the two periods, the simulations predict on average a gross primary production (GPP) increase of 513 g(C) m 2 (+38%). This increase is relatively steep until 2020, followed by a slowing down of the GPP rise due to an increase of the effect of water stress. Contrary to GPP, the ecosystem respiration (Reco ) raises at a constant rate (350 g(C) m 2 i.e. 31% from 1960 to 2100). The dynamics of the net ecosystem productivity (GPP minus Reco ) is the consequence of the effect on both GPP and Reco and differs per site. The ecosystems always remain carbon sinks; however the sink strength globally decreases for coniferous (8%), increases for sclerophyllous evergreen (+34%) and strongly increases for deciduous forest (+67%) that largely beneﬁts by the lengthening of the foliated period. The separately quantiﬁed effects of the main variables (temperature, length of foliated season, CO2 fertilization, drought effect), show that the magnitude of these effects depends on the species and the climatic zone
Keywords: canopy scale; carbon sink; climate change; forest ecosystems; Phenology

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber - Díaz-Fernández, Pedro M.; Climent, José; Gil, Luis (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed
Keywords: Cork oak; iberian peninsula; Phenology; quiescent flowers; ripening cycle

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber - Díaz-Fernández, Pedro M; Climent, José; Gil, Luis (Trees, 2004)
Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was assessed in seven cork oak stands, covering a wide range of environmental conditions. In each stand, 100 individuals were sampled once in spring and once in autumn. Biennial acorns were observed with variable frequencies in all populations. There was a significant and positive relationship between latitude and the percentage of trees with biennial acorns within northern and central populations. On the contrary, this trend was not significant among southern populations. The hypothesis that the presence of biennial acorns in Quercus suber is related to individual female flowering phenology was confirmed in four populations located in the southwestern Iberian Peninsula. Unregarding local differences in the distribution of phenological stages anticipated trees bore significantly less biennial acorns than delayed individuals of the same stand. This result is coherent with the idea that the length of the vegetative period plays a crucial role in the frequency of annual and biennial acorn ripening patterns. The relationship between annual and biennial ripening cycles and the multiple acorn crops is discussed
Keywords: Cork oak; iberian peninsula; Phenology; quiescent flowers; ripening cycle

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L; Tognetti, Roberto; Bräker, Otto U; Schoch, Werner; Innes, John L (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Análise da Estratégia Fenodinâmica de Cistus salvifolius em Três Locais Distintos (Pinhal de Leiria, Cabeção e Odemira) - Borges, Ana Eleonora; de Almeida, Victor Valente; da Silva, António Morais (Silva Lusitana, 2002)
We describe the phenomorphological strategy of Cistus salvifolius found in pine woods of the Leiria region and in cork oak woodlands of Alentejo (Cabeção and Odemira north and Odemira south). An analysis is made of the evolution of the biological cycle as a function of climatic changes
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: ecomorphology; edaphic factors; Phenology; srubs; underground

Análise da Estratégia Fenodinâmica de Cistus salvifolius em Três Locais Distintos (Pinhal de Leiria, Cabeção e Odemira) - Borges, Ana Eleonora; de Almeida, Victor Valente; da Silva, António Morais (Silva Lusitana, 2002)
We describe the phenomorphological strategy of Cistus salvifolius found in pine woods of the Leiria region and in cork oak woodlands of Alentejo (Cabeção and Odemira north and Odemira south). An analysis is made of the evolution of the biological cycle as a function of climatic changes
Keywords: ecomorphology; edaphic factors; Phenology; srubs; underground

Modelling start of oak pollen season in different climatic zones in Spain - García-Mozo, H.; Galan, C.; Aira, M. J. (Agricultural and Forest Meteorology, 2002)
Quercus pollen and meteorological data for several years from eight sites in Spain have been statistically analysed to select the threshold temperature and calculate the mean heat accumulation for predicting the Quercus pollination start in different climatic areas. The growing degree days method, which assumes the daily temperature varies as a sine wave, was used for heat accumulation calculations. Threshold temperatures between 4 and 12 ◦ C were chosen using linear regression equations forced through the origin and their root mean square error (RMSE) of predicted against the observed dates for each observation site. Above the threshold, the average growing degree days (up to 1999) for the studied years was taken as the predictor value. Results showed a relationship between the selected threshold and elevation and a stronger and statistically signiﬁcant correlation between threshold and yearly mean temperature, for each site. Regression analysis indicated that the selected threshold and the calculated heat accumulation were optimum for most of the localities. The validity of the results was tested using the meteorological data for the year 2000 as independent variable and this conﬁrmed that there were only a few days difference between the predicted and observed day of the ﬁrst pollen release for most of the studied localities
Keywords: Aerobiology; oak forest; Phenology; pollen; threshold temperature

Modelling start of oak pollen season in different climatic zones in Spain - García-Mozo, H; Galán, C; Aira, M J (Agricultural and Forest Meteorology, 2002)
Quercus pollen and meteorological data for several years from eight sites in Spain have been statistically analysed to select the threshold temperature and calculate the mean heat accumulation for predicting the Quercus pollination start in different climatic areas. The growing degree days method, which assumes the daily temperature varies as a sine wave, was used for heat accumulation calculations. Threshold temperatures between 4 and 12 ◦ C were chosen using linear regression equations forced through the origin and their root mean square error (RMSE) of predicted against the observed dates for each observation site. Above the threshold, the average growing degree days (up to 1999) for the studied years was taken as the predictor value. Results showed a relationship between the selected threshold and elevation and a stronger and statistically signiﬁcant correlation between threshold and yearly mean temperature, for each site. Regression analysis indicated that the selected threshold and the calculated heat accumulation were optimum for most of the localities. The validity of the results was tested using the meteorological data for the year 2000 as independent variable and this conﬁrmed that there were only a few days difference between the predicted and observed day of the ﬁrst pollen release for most of the studied localities
Keywords: Aerobiology; oak forest; Phenology; pollen; threshold temperature

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M F; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M. F.; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). - García-mozo, Herminia; Hidalgo, Pablo J; Galán, Carmen; Gómez-Casero, Maria Teresa; Domínguez, Eugenio (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]
Keywords: CATKIN-bearing plants; Cork oak; flowers; Fruit; Phenology; PLANT spores; POLLEN (citation)

Catkin frost damage in Mediterranean cork-oak (Quercus suber L.). - García-mozo, Herminia; Hidalgo, Pablo J.; Galán, Carmen; Gómez-Casero, Maria Teresa; Domínguez, Eugenio (Israel Journal of Plant Sciences, 2001)
During a period of study of floral phenology and pollen production in the cork-oak, Quercus suber L. (199799), an interruption of catkin development was detected in spring 1998. The cause might have been a sharp drop in minimum temperatures during that period, which coincided with the initial stages of microsporogenesis. Results show that environmental temperatures close to 0 ºC halted microsporogenesis and catkinelongation, resulting in their complete death. No fruits were observed in the affected zone, as a possible consequence of the lack of pollen. Phenological, histological, andaerobiological data are analyzed as a whole in order to gain a better understanding of the phenomenon. Cold spells during flowering may be one of the factors influencing the high interannual variability of acorn production in Quercus species. [ABSTRACT FROM AUTHOR]
Keywords: CATKIN-bearing plants; Cork oak; flowers; Fruit; Phenology; PLANT spores; POLLEN (citation)

The effect of cork removal on the radial growth and phenology of young cork oak trees - Fialho, C.; Lopes, F.; Pereira, H. (Forest Ecology and Management, 2001)
The effect of the removal of cork was studied in 11-years old cork oak trees (Quercus suber L.), growing in favorable conditions, in relation to phenology and radial growth during two years. Longevity of leaves was 14±15 months (1996, 1998) and 10 months (1997). Bud burst started in mid-February and leaf ¯ushing in April, extending until June. Neither a distinct two-period ¯ushing nor an autumn bud burst or leaf ¯ushing were observed. Radial growth started in mid-April and continued until the end of November, with the maximum growth in June and July. In trees with the removal of cork, leaf abscission occurred a little earlier and new branches had on average 23% fewer new leaves. The radial growth of the trees and its general seasonal pattern were not affected by cork removal in the year of removal or in the year after. The only observation was a shift of the maximum radial growth rate from June to July for the trees where cork had been removed
Keywords: cork removal; cork-oak; Phenology; Quercus suber; Radial growth

The effect of cork removal on the radial growth and phenology of young cork oak trees - Fialho, C; Lopes, F; Pereira, H (Forest Ecology and Management, 2001)
The effect of the removal of cork was studied in 11-years old cork oak trees (Quercus suber L.), growing in favorable conditions, in relation to phenology and radial growth during two years. Longevity of leaves was 14±15 months (1996, 1998) and 10 months (1997). Bud burst started in mid-February and leaf ¯ushing in April, extending until June. Neither a distinct two-period ¯ushing nor an autumn bud burst or leaf ¯ushing were observed. Radial growth started in mid-April and continued until the end of November, with the maximum growth in June and July. In trees with the removal of cork, leaf abscission occurred a little earlier and new branches had on average 23% fewer new leaves. The radial growth of the trees and its general seasonal pattern were not affected by cork removal in the year of removal or in the year after. The only observation was a shift of the maximum radial growth rate from June to July for the trees where cork had been removed
Keywords: cork removal; cork-oak; Phenology; Quercus suber; Radial growth

Comparative photochemical and phenomorphological responses to winter stress of an evergreen ( Quercus ilex L.) and a semi-deciduous ( Cistus albidus - Oliveira, G; Penuelas, J (Acta Oecologica, 2000)
The impact of winter stress on plants from a Mediterranean area was evaluated through comparison of photosystem II (PS II) efficiencies and phenomorphological characteristics of two Mediterranean woody species – Quercus ilex (evergreen) and Cistus albidus (semi-deciduous). The studies were carried out in NE Spain, at two sites with different mean winter temperatures. The results showed that reductions of the efficiency of PS II may occur in Mediterranean plant communities during winter, and are especially remarkable on colder days. The extent and duration of the decrease in PS II efficiency (photoinhibition) depended not only on the climatic conditions, but also on the site, on the species considered and on the position of leaves in the plant canopy. Increased photoinhibition at the colder site was only clear for C. albidus. Nevertheless, the efficiencies of PS II were always higher in C. albidus than in Q. ilex. Phenological patterns, morphology and leaf inclination may protect C. albidus leaves from potentially photoinhibitory conditions in winter. Morphological and structural photoprotection is apparently not so well developed in Q. ilex, which probably relies more on increased protection at the photochemical level of its long-lived leaves. As has been reported in relation to summer-drought stress, Q. ilex has possibly developed a strategy of tolerance to photoinhibition, whereas C. albidus relies preferentially on avoidance features
Keywords: Chlorophyll ﬂuorescence; evergreens; leaf characteristics; Mediterranean winter; Phenology; photoinhibition; semi-deciduous

Water stress responses of seedlings of four Mediterranean oak species - Fotelli, M N; Radoglou, K M; Constantinidou, H.-I. A (Tree Physiology, 2000)
Effects of water stress on phenology, growth, stomatal activity and water status were assessed from April to November 1996 in 2-year-old seedlings of Quercus frainetto Ten. (Quercus conferta Kit.), Quercus pubescens Willd., Quercus macrolepis Kotschy (Quercus aegilops auct.) and Quercus ilex L. growing in containers in northern Greece. All four species developed more than 50% of their total leaf area before the beginning of June—an adaptation to arid climates. Well-irrigated plants tended to develop greater individual leaf area, number of leaves per plant, total plant leaf area, height and root:shoot ratios than water-stressed plants, but the difference between treatments was not significant for any parameter in any species. Quercus macrolepis appeared to be the most drought-tolerant of the four species. It maintained the highest number of leaves of the smallest size and increased the proportion of fine roots during drought. In all species, drought caused significant decreases in stomatal conductance and predawn and midday water potentials from mid-July until the end of August, when the lowest soil water content and highest mean daily air temperatures and midday leaf temperatures occurred; however, the responses were species-specific. Among the four species, Quercus macrolepis sustained the highest stomatal conductance despite very low water potentials, thus overcoming drought by means of desiccation tolerance. Quercus ilex decreased stomatal conductance even before severe water stress occurred, thereby avoiding dessication during drought. Quercus pubescens had the highest water potential despite a high stomatal conductance, indicating that its leaf water status was independent of stomatal activity. Quercus frainetto was the least drought-resistant of the four species. During drought it developed very low water potentials despite markedly reduced stomatal aperture.
10.1093/treephys/20.16.1065
Keywords: Growth; Phenology; Quercus; Stomatal conductance; water potential

Collembola populations under sclerophyllous coppices in Provence (France): comparison between two types of vegetation, Quercus ilex L. and Quercus coccifera L. - Cortet, Jérôme; Poinsot-Balaguer, Nicole (Acta Oecologica, 1998)
A comparative analysis of soil Collembola using two types of sclerophyllous vegetation (Quercus ilex and Quercus cocc@ru) was performed at a calcareous site in Provence (France). Collembola populations were examined over a one-year period (1 I successive months) in three different soil layers. Although no statistically significant differences could be observed for Collembola abundance and diversity, multivariate analyses (FCA) differentiated the two coppices. Phenologies of some species showed specific responses to the microclimate induced by edaphic conditions. Even though the two coppices were sclerophyllous, the structure of each vegetation, the quantity and quality of litter, which were dif- ferent, could influence environmental conditions and thus the dynamics of collembolan populations.
Keywords: Collembola; litter decomposition; Phenology; Quercus coccifera; Quercus ilex

Collembola populations under sclerophyllous coppices in Provence (France): comparison between two types of vegetation, Quercus ilex L. and Quercus coccifera L. - Cortet, Jérôme; Poinsot-Balaguer, Nicole (Acta Oecologica, 1998)
A comparative analysis of soil Collembola using two types of sclerophyllous vegetation (Quercus ilex and Quercus cocc@ru) was performed at a calcareous site in Provence (France). Collembola populations were examined over a one-year period (1 I successive months) in three different soil layers. Although no statistically significant differences could be observed for Collembola abundance and diversity, multivariate analyses (FCA) differentiated the two coppices. Phenologies of some species showed specific responses to the microclimate induced by edaphic conditions. Even though the two coppices were sclerophyllous, the structure of each vegetation, the quantity and quality of litter, which were dif- ferent, could influence environmental conditions and thus the dynamics of collembolan populations.
Keywords: Collembola; litter decomposition; Phenology; Quercus coccifera; Quercus ilex

The effect of drought on gas exchange and water potential in leaves of seven Mediterranean woody species - Gucci, R; Massai, R; Casano, S; Gravano, E; Lucchesini, M (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The water relations and gas exchange parameters of Arbutus unedo, Cistus monspeliensis, Erica arborea, Myrtus communis, Phillyrea latifolia, Pistacia lentiscus, and Quercus ilex growing in the shrubland vegetation at the Parco Naturale della Maremma (Italy), were studied over two consecutive years. At high leaf water potentials, photosynthetic rates and stomatal conductance were relatively low in all species but C. monspeliensis. Stomatal conductance remained relatively high in C. monspeliensis leaves as soil moisture was depleted, whereas A. unedo, E. arborea, M. communis, and P. lentiscus were more conservative in water use. P. latifolia and Q. ilex showed a drought-tolerant behaviour.
Keywords: Drought tolerance; leaf water potential; Phenology; Stomatal conductance

Ecophysiological studies of Mediterranean plant species at the Castelporziano estate - Manes, Fausto; Seufert, Günther; Vitale, Marcello (Atmospheric Environment, 1997)
e aim of this work was to characterize the eco-physiological performance of the main plant species of the Castelporziano site by single leaf investigations. We measured the leaf gas exchange of Quercus ilex L., Pinus pinea L., Pistacia lentiscus L. and Asphodelus microcarpus L. for several days. Additionally, the xylem water potential of Quercus ibex, Pinus pinea and Pistacia lentiscus was recorded in order to obtain more physiological background information for the discussion of the trace gas emissions. This study indicates significantly different physiological responses to the different environmental condi- tions. In particular, summer conditions (high values of light, air temperature and low xylem water potentials) caused the depression of photosynthesis in Quercus ibex and Pinus pinea but did not affect photosynthesis of Pistacia lentiscus and Asphodelus microcarpus. This should be taken into account when discussing VOC emission rates and fluxes
Keywords: fluorescence; Phenology; photosynthesis; Transpiration; VOCs; Xylem water potential

Phenological and growth patterns of the Mediterranean oak Quercus suber L. - Oliveira, Graca; Correia, Otflia (Trees-Structure and …, 1994)
The phenology of Quercus suber L., a dominant species of the montados in the Iberian Peninsula, was studied for 2 years in southwest Portugal. The seasonal progression of phenological events was analyzed in seven trees. Selected branches were examined monthly for shoot elongation, leaf number, branching, flowering, and fruiting. Radial stem growth and specific leaf weight were also studied. Active growth was observed from early spring to early summer. Reserves accumulated during winter and high photosynthetic activity in early spring apparently supported this strong development. The growth flush started with stem radial increment, which seemed to be impaired by spring rainfall. Male inflorescence production was the next phenological event. Old leaves were shed during new twig and leaf emergence. Shoot elongation and the number of new leaves produced were well correlated with the previous-year shoot's length, and were not clearly related to climatic factors. Radial growth resumed in au- tumn at a lower rate than in the previous spring, a possible consequence of a reserve depletion due to lower photo- synthetic production in summer and investment on fruit maturation, which was complete by late autumn. Premature and excessive new leaf production were apparently sub- jected to self-pruning strategies related to the development of each tree's crown. Younger cork-oaks produced shorter and fewer shoots per module, and more sclerophyllous leaves than the older ones. A high intra-specific variability was observed in all the results.
Keywords: Growth; Phenology; Quercus suber; specific leaf weight; Trees

Phenological and growth patterns of the Mediterranean oak Quercus suber L. - Oliveira, Graca; Correia, Otflia (Trees-Structure and …, 1994)
The phenology of Quercus suber L., a dominant species of the montados in the Iberian Peninsula, was studied for 2 years in southwest Portugal. The seasonal progression of phenological events was analyzed in seven trees. Selected branches were examined monthly for shoot elongation, leaf number, branching, flowering, and fruiting. Radial stem growth and specific leaf weight were also studied. Active growth was observed from early spring to early summer. Reserves accumulated during winter and high photosynthetic activity in early spring apparently supported this strong development. The growth flush started with stem radial increment, which seemed to be impaired by spring rainfall. Male inflorescence production was the next phenological event. Old leaves were shed during new twig and leaf emergence. Shoot elongation and the number of new leaves produced were well correlated with the previous-year shoot's length, and were not clearly related to climatic factors. Radial growth resumed in au- tumn at a lower rate than in the previous spring, a possible consequence of a reserve depletion due to lower photo- synthetic production in summer and investment on fruit maturation, which was complete by late autumn. Premature and excessive new leaf production were apparently sub- jected to self-pruning strategies related to the development of each tree's crown. Younger cork-oaks produced shorter and fewer shoots per module, and more sclerophyllous leaves than the older ones. A high intra-specific variability was observed in all the results.
Keywords: Growth; Phenology; Quercus suber; specific leaf weight; Trees

INFLUENCIA DE LA POSICION DE LA COPA SOBRE LA FENOLOGIA y LAS RELACIONES HIDRICAS DEL ALCORNOQUE (QUERCUS SUBER L.) - Oliveira, G; Werner, C; Mertens, C; Correia, O (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
A tree crown may be seen as a large and heterogeneous population of branches and leaves, unequally subjected to the environmental factors. It is thus questionable if studies on a few leaves or a branch will be a good approach to the whole canopy. This is particularly important in the field, where the applieation of ecophysiological measurements to mature (and generally large) trees presents obvious human and financial problems. The purpose of this study was to determine the effeet of different levels and directions within the' crown on the phenology and water relations of a typieal cork-oak in south Portugal. Our preliminary results show that the parts of the erown exposed to higher radiation value~ present a stronger growth and biomass production (direetion effect). Crown level was not clearly related to the results, suggesting that the "height effect" is not very important in trees with wide and diffuse crowns like the ones occurring in the montado systems.
Keywords: Crown position; Phenology; Quercus suber; Stomatal eonductance 1)

INFLUENCIA DE LA POSICION DE LA COPA SOBRE LA FENOLOGIA y LAS RELACIONES HIDRICAS DEL ALCORNOQUE (QUERCUS SUBER L.) - Oliveira, G.; Werner, C.; Mertens, C.; Correia, O. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
A tree crown may be seen as a large and heterogeneous population of branches and leaves, unequally subjected to the environmental factors. It is thus questionable if studies on a few leaves or a branch will be a good approach to the whole canopy. This is particularly important in the field, where the applieation of ecophysiological measurements to mature (and generally large) trees presents obvious human and financial problems. The purpose of this study was to determine the effeet of different levels and directions within the' crown on the phenology and water relations of a typieal cork-oak in south Portugal. Our preliminary results show that the parts of the erown exposed to higher radiation value~ present a stronger growth and biomass production (direetion effect). Crown level was not clearly related to the results, suggesting that the "height effect" is not very important in trees with wide and diffuse crowns like the ones occurring in the montado systems.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: Crown position; Phenology; Quercus suber; Stomatal eonductance 1)

INFLUENCIA DE LA POSICION DE LA COPA SOBRE LA FENOLOGIA y LAS RELACIONES HIDRICAS DEL ALCORNOQUE (QUERCUS SUBER L.) - Oliveira, G; Werner, C; Mertens, C; Correia, O (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
A tree crown may be seen as a large and heterogeneous population of branches and leaves, unequally subjected to the environmental factors. It is thus questionable if studies on a few leaves or a branch will be a good approach to the whole canopy. This is particularly important in the field, where the applieation of ecophysiological measurements to mature (and generally large) trees presents obvious human and financial problems. The purpose of this study was to determine the effeet of different levels and directions within the' crown on the phenology and water relations of a typieal cork-oak in south Portugal. Our preliminary results show that the parts of the erown exposed to higher radiation value~ present a stronger growth and biomass production (direetion effect). Crown level was not clearly related to the results, suggesting that the "height effect" is not very important in trees with wide and diffuse crowns like the ones occurring in the montado systems.
Keywords: Crown position; Phenology; Quercus suber; Stomatal eonductance 1)

Aproveitamento de plantas espontâneas (aromáticas e mediciais), em montado de sobro - Lopes Borges, A. E.; Afonso Morais, M. H.; Bernardo, A.; Azevedo Gomes, A.; Saraiva Lopes, A. M. (Scientia gerundensis, 1992)
In a previous paper the phenological evolution of aromatic and medicinal species in the understory of open forest of cork oak was studied, localised in two <<vis-a-visn hillsides with NW and SE exposition in Odemira. In this paper the effect of exposition in biological cycle of species is apreciated. A comparative analysis between the vegetation of the two stations was made in funtion of the phenological evolution, biomass prodution, floristic list and recovery by species. The characteristic of the organic and inorganic fractions are emphasized related with the present phenophases.
Keywords: aromatic plants; biomass; cork-oak stands; Medicinal plants; Phenology

Aproveitamento de plantas espontâneas (aromáticas e mediciais), em montado de sobro - Lopes Borges, A E; Afonso Morais, M H; Bernardo, A; Azevedo Gomes, A; Saraiva Lopes, A M (Scientia gerundensis, 1992)
In a previous paper the phenological evolution of aromatic and medicinal species in the understory of open forest of cork oak was studied, localised in two <<vis-a-visn hillsides with NW and SE exposition in Odemira. In this paper the effect of exposition in biological cycle of species is apreciated. A comparative analysis between the vegetation of the two stations was made in funtion of the phenological evolution, biomass prodution, floristic list and recovery by species. The characteristic of the organic and inorganic fractions are emphasized related with the present phenophases.
Keywords: aromatic plants; biomass; cork-oak stands; Medicinal plants; Phenology

ORGANIZACION Y VARIACIONES ESTACIONALES DEL ÁPICE VEGETATIVO DEL ALCORNOQUE - Molinas, M; Oliva, P; Vázquez, M Oliva P (Scientia gerundensis, 1989)
This paper is directed to the basic understand of organization and seasonal changes in the vegetative buds of the cork-oak through the study of the phenology and the histology of a branch during to annual cycles. During the period under study, two sprouting seasons succeded each year; one sprouting was allways in the middle of the spring and the other one either in the summer or in the fall. The elongation of the branch segments was characteristic of a cork-oak in juvenil phase. The hight value of the whole growth should be noticed. The cork oak produces both short and long shoots. Long shoots occur at the apex and distal portions of branches. The long and short shoots differ in number of leaves but not in internode elongation. Elongation depend on the shoot vigor and position. There is a good correlation between elongation and number of leaves per segment. Buds show seasonal changes. A rest phase, a bud expansion phase and a new bud formation phase partially omerlaping the bud expansion phase can be distinguished. Cork-oak vegetative buds show a tunica and corpus type of cellular zonation which corresponds to the Type I of the Gifford and Carson (1971) classification. Only lowermost leaves ovenvinter in the bud. This may explain the maked heteroblastia of the leaves in the shoots. The seasonal study shows that maximum cytohistological zonation occurs near the end of rapid shoot elongation.
Keywords: bud morphology; cork-oak; Phenology; Quercus suber; shoot elongation

Successional changes in the morphology and ecological responses of a grazed pasture ecosystem in Central Spain - Sal, A Gomez; Miguel, J M; Casado, M A; Pineda, F D (Plant Ecology, 1986)
Morphological characteristics related to spatial occupation, reproduction and adaptations to grazing were used to characterize the most frequent species in a therophytic pastureland of Central Spain. Periodic ploughing is a traditional practice in these pastures and allows observation of successional change. In the present study, four neighbouring slopes of differing time since last ploughing were chosen. Species biomass was measured at different times during the annual growing season for two different slope positions. Grazing pressure is an important environmental factor affecting ecosystem organization, the most palata- ble plants tending to show increasing biomass with succession. In the most mature stages, there is a predomi- nance of species characterized by horizontal occupation of space and sprouting after mowing or grazing. During succession segregation of the different morphological characteristics occurs in slope sectors related to geomorphological dynamics. Similarly, phenological development tends to be later in pastures in the lowest slope zones, due probably to their greater summer soil moisture content.
Keywords: ecosystem exploitation; Grazing; herbivore; mediterranean pasture; Phenology; phytomass; Plant morphology; succession

Note floristiche e fenologiche nel territorio di Arneo (Fra Taranto e Gallipoli) - Ferente, Adriana (Giornale botanico italiano, 1952)
Summary The author describes the vegetation and phenology of a Quercus Ilex wood in the Comprensorio dell'Arneo, betwen Taranto and Gallipoli along the eastern shore of the Ionian Sea (Golfo di Taranto). The wood consists partly of a degraded bushy vegetation. The wood was visited eleven times during the year and each time species found flowering were noted (Table at pp 296?301): the greatest number of them, many being therothytes, was found on April 21rst (fig. 2) with about a month's delay in comparison with Palestine (Gindel). In May there is a considerable i decrease in number of species flowering. In summer and winter, because of drought and low temperature very few species, mostly geophytes, were found flowering, and only slightly but markedly more in Autum.
The following values have no corresponding Zotero field: publisher: Taylor & Francis
Keywords: Phenology; Quercus ilex; Taranto Golf